2006
DOI: 10.1007/s10753-006-9010-2
|View full text |Cite
|
Sign up to set email alerts
|

An Extract of the Medicinal Mushroom Agaricus blazei Murill Differentially Stimulates Production of Pro-inflammatory Cytokines in Human Monocytes and Human Vein Endothelial Cells in vitro

Abstract: An extract of the edible mushroom Agaricus blazei Murill (AbM) has known antitumor and anti-infection properties, probably mainly by stimulating mononuclear phagocytes of the native immune system. The aim of this work was to study the effect of AbM on the production by human monocytes and human umbilical vein endothelial cells (EC) of pro-inflammatory cytokines (IL-1beta, IL-6, IL-8, TNFalpha), the anti-inflammatory/T regulatory cytokine IL-10 and the pro-Th1 cytokine IL-12. AbM, in concentrations from 1-15%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 31 publications
6
40
1
1
Order By: Relevance
“…DC kill microbes, stimulate Th cells and regulate B cell Ig production [28]. AbM has been shown by others and us to have stimulatory effects in vitro on the production of proinflammatory cytokines in immune cells, including monocytic cells and MDDC [29][30][31]. The main purpose of the present study was to examine the modulatory effect of AbM on cell surface markers in MDDC.…”
Section: Introductionmentioning
confidence: 99%
“…DC kill microbes, stimulate Th cells and regulate B cell Ig production [28]. AbM has been shown by others and us to have stimulatory effects in vitro on the production of proinflammatory cytokines in immune cells, including monocytic cells and MDDC [29][30][31]. The main purpose of the present study was to examine the modulatory effect of AbM on cell surface markers in MDDC.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that edible mushrooms and their extract has the gram negative/positive activity of bacteria, yeast and filamentous fungi Numerous studies have shown that edible fungi and its extract has the activity to resistance of gram negative/positive, yeast and filamentous fungi [12]. Bernardshaw, et al studies have demonstrated that agaricus blazei murill extract can kill pneumococcus 6B in mice [13].…”
Section: Antifungalmentioning
confidence: 99%
“…Reverse transcriptase and protease are the key enzymes of HIV-1 life cycle, and versicolor polysaccharides can inhibit their activity. And also some of ganoderma lucidum triterpenoid compounds with anti-HIV-1-protease activity [12]. Maitake mushroom extracts can inhibit the hepatitis B, herpes simplex virus, and the active of the influenza virus.…”
Section: Anti-viralmentioning
confidence: 99%
“…Polysaccharides are the best known and most potent mushroom-derived substances with antitumour and immunomodulating properties (Borchers, Keen, & Gershwin, 1999;Mizuno, Minato, & Ito, 1999;Ooi & Liu, 1999;Reshetnikov, Wasser, & Tan, 2001;Tzianabos, 2000;Wasser, 1999;Wasser, 2002). The major immunomodulatory effects of the polysaccharides include mitogenicity and activation of immune cells, such as lymphocytes, macrophages, dendritic cells and natural killer (NK) cells, resulting in the cytokines production (Bernardshaw, Hetland, Ellertsen, Tryggestad, & Johnson, 2005;Fujimiya et al, 1998;Lull, Wichers, & Savelkoul, 2005;Sorimachi, Akimoto, Ikehara, Inafuku, & Yamazaki, 2001;Wasser, 2002).…”
Section: Introductionmentioning
confidence: 99%